PENDAMPINGAN PASTORAL MENGHADAPI KEMATIAN DALAM PERJUMPAAN KEJADIAN 27:1-29 DAN BUDAYA BATAK MANULANGI NATUA-TUA - Firman Panjaitan; Daniel Irwanto Sinabariba (Melo: Jurnal Studi Agama-agama, 2022)
Pastoral service is an important task of the church to maintain the life of the congregation, therefore pastoral assistance is always aimed at life. One form of church pastoral service that has received less attention is assistance to people who are facing death, even though this kind of assistance is highly expected because when facing death someone will be faced with anxiety and fear. The Genesis 27:1-19 narrative highlights the importance of feeding people who are facing death as a form of the child/family's ability to continue to be companions. This story has parallels with the Manulangi Natua-tua culture in the Batak tribe, where through this culture each family member will provide certainty to parents who are facing death that they will still be there to accompany them, so that parents do not need to be afraid and anxious to face death. This study uses a qualitative method, with a narrative interpretation approach to Genesis 27:1-19 and literature research on Batak culture. The results of the study show that mentoring people who are facing death is an important thing that must be done by the church as a form of the church's responsibility towards life.